2021
DOI: 10.1016/j.cmi.2020.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests for infectious diseases in the emergency department

Abstract: 36Background: Rapid diagnostic tests (RDTs) for infectious diseases, with a turn-around time 37 <2 hours, are promising tools that could improve patient care, antimicrobial stewardship and 38 infection prevention in the emergency department (ED) setting. Numerous RDTs have been 39 developed but not necessarily for the ED environment. Their successful implementation in 40 the ED relies on their performance and impact on patient management. 41Objectives: The aim of this narrative review is to provide an overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 78 publications
(1 reference statement)
0
26
0
Order By: Relevance
“…The diagnosis of most of these viruses is based on molecular techniques that can only be performed at specialized referral centers. Recently, there has been increased interest in using POCTs in other settings, such as emergency departments, although implementation might be hampered by the need for specific training (Bouzid et al, 2020). NAATs have higher sensitivity than immunochromatographic assays, but generally, they require a higher degree of technical skills and training (Drancourt et al, 2016).…”
Section: Commercially Available Test Systemsmentioning
confidence: 99%
“…The diagnosis of most of these viruses is based on molecular techniques that can only be performed at specialized referral centers. Recently, there has been increased interest in using POCTs in other settings, such as emergency departments, although implementation might be hampered by the need for specific training (Bouzid et al, 2020). NAATs have higher sensitivity than immunochromatographic assays, but generally, they require a higher degree of technical skills and training (Drancourt et al, 2016).…”
Section: Commercially Available Test Systemsmentioning
confidence: 99%
“…Clinicians should also be aware that clinical validation studies have assessed the performance of some respiratory panels with suboptimal approaches and reported cumulative performance results or positive and negative percentage agreement as surrogates of sensitivity and specificity [10]. Notably, certain panels encompass bacterial targets that have been validated with fewer than ten positive samples, and performance has sometimes been reported to be lower than that for viral targets [10]. Thus, clinicians should be particularly attentive when interpreting cumulative performance results or percentage agreement values, which may represent an important and underappreciated limitation.…”
Section: To the Editormentioning
confidence: 99%
“…POC tests based on the detection of pathogen nucleic acids (NAs), antigens, or even antibodies have been developed for a variety of infectious diseases [13,28]. Regarding STIs, POC tests are available for CT [29], NG [30], and TV [31], for example.…”
mentioning
confidence: 99%
“…Recent systematic reviews have shown that, in many instances, the use of POCs can result in a substantial reduction in both missed treatments and overtreatment [28,36]. Treatment uptake is also improved, and patients show appreciation for receiving a quick and specific diagnosis, which also facilitates the treatment of the partners of patients [37].…”
mentioning
confidence: 99%